Wyznacz A':
1. A=<-1;2>
2. A=(-2;4>
3. A=( - nieskończoności ; 4)

Wyznacz A^(do)B:
1.A=<-1;3> B=<1;4>
2. A=(0;2) B=<-2;3)
3. A=( - nieskończoności; 3> B=<3;4)
4. A=<2;6) B=<6;7>
5. A=(-4; + nieskończoności) B=(-3; + nieskończoności)
6. A=(- nieskończoności; 4) B=<0; + nieskończoności)

3

Odpowiedzi

2009-09-05T12:44:54+02:00
A'
1. A'=(-nieskończoności;-1)w sumie z(2;nieskończoności)
2. A'=(-nieskończoności;-2>w sumie z (4;nieskończoności)
3. A'= <4;nieskończoności)

A^B
1. A^B=<1;3>
2. A^B=(0;2)=A
3. A^B={3}
4. A^B=zbiór pusty
5. A^B=(-3; + nieskończoności)=B
6. A^B=(0;4)
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-09-05T12:53:56+02:00
A'
u niech oznacza sume
1. A'=(-∞;-1) u <2;+∞)
2. A'=(-∞;-2> u (4;+∞)
3. A'= <4;+∞)

A^B
1. A^B=<1;3>
2. A^B=(0;2)=A
3. A^B={3}
4. A^B=zbiór pusty
5. A^B=(-3; +∞)=B
6. A^B=(0;4)
2009-09-05T12:57:51+02:00
A'
1. A' = (-∞ ; -1) u <2 ; ∞)
2. A' = (-∞ ; -2> u (4 ; ∞)
3. A' = <4 ; +∞)

A^B
1. A^B = <1 ; 3>
2. A^B = (0 ; 2)=A
3. A^B = {3}
4. A^B = zbiór pusty
5. A^B = (-3 ; ∞)=B
6. A^B = (0 ; 4)